85.7k views
5 votes
Complete the square to transform the quadratic equation into the form (x – p)2 = q. x2 - 12x - 5 = 7 A) (x - 36)2 = 9 B) (x - 6)2 = 48 C) (x - 36)2 = -9 D) (x - 6)2 = -48

(May I have an explanation or work that you did)

2 Answers

4 votes

Answer:

B

Explanation:

given

x² - 12x - 5 = 7 ( add 5 to both sides )

x² - 12x = 12

To complete the square

add (half the coefficient of the x- term )² to both sides

x² + 2(- 6)x + (- 6)² = 12 + (- 6)²

x² + 2(- 6)x + 36 = 12 + 36 ← complete the square on the left side

(x - 6)² = 48 → B

User Andy Mortimer
by
5.2k points
3 votes

x2 - 12x - 12 = 0

(x - 6)2 - 48 = 0

(x - 6)2 = 48

Hence, the answer is (B).

User Whichdan
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.